Effect of hand paddles and parachute on butterfly coordination - Telles, T.; Barroso, R.; Carvalho Barbosa, A.; Salgueiro, D. F. D. S.; Colantonio, E.; Júnior, O. A. (Journal of Sports Sciences, 2015)
This study investigated the effects of hand paddles, parachute and hand paddles plus parachute on the inter-limb coordination of butterfly swimming. Thirteen male swimmers were evaluated in four random maximal intensity conditions: without equipment, with hand paddles, with parachute and with hand paddles + parachute. Arm and leg stroke phases were identified by 2D video analysis to calculate the total time gap (T1: time between hands` entry in the water and high break-even point of the first undulation; T2: time between the beginning of the hand`s backward movement and low break-even point of the first undulation; T3: time between the hand`s arrival in a vertical plane to the shoulders and high break-even point of the second undulation; T4: time between the hand`s release from the water and low break-even point of the second undulation). The swimming velocity was reduced and T1, T2 and T3 increased in parachute and hand paddles + parachute. No changes were observed in T4. Total time gap decreased in parachute and hand paddles + parachute. It is concluded that hand paddles do not influence the arm-to-leg coordination in butterfly, while parachute and hand paddles + parachute do change it, providing a greater propulsive continuity.